Rhabdomyolysis and acute renal failure after strenuous exercise and alcohol abuse: case report and literature review - Daher, Elizabeth De Francesco; Silva Júnior, Geraldo Bezerra da; Brunetta, Denise Menezes; Pontes, Lícia Borges; Bezerra, Glaydcianne Pinheiro (São Paulo Medical Journal, 2005)
CONTEXT: Rhabdomyolysis is a severe and life- threatening condition in which skeletal muscle is damaged. Acute renal failure due to rhab- domyolysis has been widely described and its main pathophysiological mechanisms are renal vasoconstriction, intraluminal cast formation and direct myoglobin toxicity. OBJECTIVE: To report on a case of acute renal failure (ARF) induced by rhabdomyolysis due to strenuous exercise and alcohol abuse and to de- scribe the pathophysiology of this type of ARF. CASE REPORT: A 39-year-old man arrived at the hospital emergency service with swollen legs and lower extremity compartment syndrome. He was oliguric and had serum creatinine and urea levels of 8.1 mg/dl and 195 mg/dl, respectively. The diagnosis of rhabdomyolysis was made through clinical and laboratory ﬁndings (creatine kinase activity of 26320 IU/l). The initial treatment consisted of ﬂuid replacement and forced diuresis. The speciﬁc treatment for compartment syndrome, such as fasciotomy, was avoided in order to prevent infection. Partial recovery of re- nal function was recorded, after ten hemodialysis sessions. Complete recovery was observed after two months of follow-up.